1980
DOI: 10.1111/j.2042-3306.1980.tb02290.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and sweat electrolyte concentrations in the horse during long distance exercise

Abstract: Summary Blood samples were taken from 20 horses competing in a 100 km endurance ride and plasma concentrations of sodium, potassium, chloride, bicarbonate and protein measured. Measurements were performed on samples taken before the ride (pre‐ride), at the mid point and end of the ride and after a 30 min recovery period (post‐ride). Sweat samples were collected from 6 horses competing in the endurance ride and 14 horses competing in a 3‐day event competition and sweat concentrations of sodium, potassium and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
46
0
6

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 5 publications
8
46
0
6
Order By: Relevance
“…According to Santos & Gonzáles (2006) the increase in lactate levels above 4 mmol/l is common on high physical intensity competition, however, despite the Marcha de Resistência be considered a low intensity competition, at the last days are developed high speeds that characterized a ratio above 4mmol/l in plasma lactate levels, similar result observed by Ferraz et al (2009) e Caiado et al (2011 In general, during endurance competitions, there are symptoms of hypokalemia associated with the fatigue of animals (Rose et al, 1980) . In this study, we observed a significant decrease in serum potassium levels (p=0.0002), but the average remained within the physiological limits.…”
Section: Discussionsupporting
confidence: 71%
“…According to Santos & Gonzáles (2006) the increase in lactate levels above 4 mmol/l is common on high physical intensity competition, however, despite the Marcha de Resistência be considered a low intensity competition, at the last days are developed high speeds that characterized a ratio above 4mmol/l in plasma lactate levels, similar result observed by Ferraz et al (2009) e Caiado et al (2011 In general, during endurance competitions, there are symptoms of hypokalemia associated with the fatigue of animals (Rose et al, 1980) . In this study, we observed a significant decrease in serum potassium levels (p=0.0002), but the average remained within the physiological limits.…”
Section: Discussionsupporting
confidence: 71%
“…Os resultados descritos na literatura são conflitantes, com alguns autores citando influência positiva ou a não interferência do exercício sobre estas variáveis sanguíne-as (Rose et al 1980, Freestone et al 1991, Balarin et al 2005, Kowal et al 2006, Padalino et al 2007.…”
Section: Introductionunclassified
“…A tendência à redução de sódio sérico em T2 observada na presente pesquisa é esperada em exercícios de longa duração, nas chamadas provas de resistência, segundo Rose et al (1980). Fernandes e Larsson (2000) comprovaram tal fato ao encontrarem concentrações de sódio após prova de enduro de 30 km com velocidade controlada (até 90 minutos após) abaixo dos valores basais para equinos da raça Mangalarga, Árabe e equinos sem raça definida (de 139,13mEq/L para 139,06mEq/L, de 140,06mEq/L para 139,60mEq/L e de 141,86mEq/L para 139,46mEq/L, respectivamente).…”
Section: Introductionunclassified